2019
DOI: 10.1029/2018wr023197
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological Model Diversity Enhances Streamflow Forecast Skill at Short‐ to Medium‐Range Timescales

Abstract: We investigate the ability of hydrological multimodel ensemble predictions to enhance the skill of streamflow forecasts at short-to medium-range timescales. To generate the multimodel ensembles, we implement a new statistical postprocessor, namely, quantile regression-Bayesian model averaging (QR-BMA). Quantile regression-Bayesian model averaging uses quantile regression to bias correct the ensemble streamflow forecasts from the individual models and Bayesian model averaging to optimally combine their probabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 91 publications
2
43
0
Order By: Relevance
“…Nevertheless, WRF-Hydro provided a more favorable forecast for Event 4, demonstrating its potential ability to predict flash floods. Overall, however, the accuracy of the WRF-Hydro forecasts was poor, supporting the findings of previous studies by Wang et al [58] and Sharma et al [31]. Figure 12 provides further statistics on the extent to which the three coupled systems contribute to an overall improvement in response to flood events.…”
Section: Results With the Wrf-hydro Modeling Systemsupporting
confidence: 78%
See 1 more Smart Citation
“…Nevertheless, WRF-Hydro provided a more favorable forecast for Event 4, demonstrating its potential ability to predict flash floods. Overall, however, the accuracy of the WRF-Hydro forecasts was poor, supporting the findings of previous studies by Wang et al [58] and Sharma et al [31]. Figure 12 provides further statistics on the extent to which the three coupled systems contribute to an overall improvement in response to flood events.…”
Section: Results With the Wrf-hydro Modeling Systemsupporting
confidence: 78%
“…Most LSM and hydrological models incorporate the same descriptions of water balance, albeit with different aims [31,32]. LSM evolves from land-atmosphere coupling models with the purpose of solving the surface energy balance equation and providing the necessary lower boundary conditions for the atmosphere [31,33]. Inversely, hydrological models focus less on radiation and more on hydrological changes (i.e., the lateral route of water along land surfaces).…”
Section: Introductionmentioning
confidence: 99%
“…The additional benefit derived from using ensembles of models for maximising skill persistence could also be assessed for different lead times and initialisation months. This is a promising avenue, as model diversity has been shown to enhance forecast skill in ensemble experiments (Sharma et al, 2019).…”
Section: Potential For Future Workmentioning
confidence: 99%
“…In their study, the dimensionality and efficiency of DDS, for example, was tested, and the authors concluded that DDS provided better results than SCE both with low-and high-dimensional problems, and is more efficient. DDS has been used to calibrate several hydrological models from simple lumped to medium level distributed models (e.g., SWAT [61,62], MESH [63], CRHM-AHM [64]) to very complicated land-surface based models (e.g., WRF-Hydro [65,66]).…”
Section: Calibration and Validationmentioning
confidence: 99%